2020
DOI: 10.14499/indonesianjpharm31iss1pp27
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of Okra Fruit (Abelmoschus esculentus (L) Moench) Extract and Fractions in Two Conditions of Diabetic Rats

Abstract: Okra (Abelmoschus esculentus (L) Moench) fruit is empirically used in type 2 diabetes mellitus treatment. This research aims to know the antihyperglycemic activity of okra fruit extract and fractions in streptozotocin-nicotinamide (STZ-NA) induced as well as in insulin resistance diabetic rats, the effect on pancreatic cells regeneration, and the effect on immunohistochemical expression of glucose transporter-4. This study used a group of 35 male Wistar rats for STZ-NA induced diabetic model and another group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Okra's flavonoid content can reduce the activity of the nuclear receptor transcription factor PPARγ, a key regulator of lipid and glucose homeostasis 19 . Flavonoids such as isoquercitin and quercitin are known to play an important role in the reduction of blood glucose and triglyceride by improving glucose tolerance and increasing lipoprotein lipase activities [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Okra's flavonoid content can reduce the activity of the nuclear receptor transcription factor PPARγ, a key regulator of lipid and glucose homeostasis 19 . Flavonoids such as isoquercitin and quercitin are known to play an important role in the reduction of blood glucose and triglyceride by improving glucose tolerance and increasing lipoprotein lipase activities [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…The inherent capacity of okra on reducing the plasma concentration of TG could be attributed to the rich content of some phytochemicals. Okra is rich in flavonoid compounds (isoquercitin and quercitin) and can reduce triglyceride levels by increasing lipoprotein lipase LPL activity 18,20,21 . Similarly, the anti-oxidant activity can limit lipid peroxidation which is vital to curbing a lot of disease conditions 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols were found to have antidiabetic potential as they inhibit dipeptidyl peptidase-4 that led to the increase of glucagon-like peptide-1 half-life, increased insulin production through direct or indirect β-cell stimulation, and increased insulin sensitivity on peripheral tissue (28), but it also improves due to diabetes complications such as kidney failure, vascular dysfunction, and others (29). Alkaloids play a role in the antidiabetic effect by causing peroxisome PPARγ, glucokinase activity, and an increase in GLUT4 (30,31). The role of terpenoids in the treatment of diabetes is to activate the AMPK fuel-sensing enzyme (Adenosin monophosphate protein kinase (AMPPK)).…”
Section: Discussionmentioning
confidence: 99%
“…17 The main flavonoid compounds, which are okra (isoquercitrin and quercetin), can reduce blood glucose levels, improve glucose tolerance and reduce triglyceride levels by increasing lipoprotein lipase (LPL) activity. [18][19] Research conducted by Ngoc in 2008 revealed that extracts of okra plants (Abelmoschus esculentus L.) could significantly reduce total cholesterol and triglyceride levels in rats. 20…”
Section: Discussionmentioning
confidence: 99%